Remediasi Dikotomi Gender melalui Profesi Drag Queen: Analisis Konten Selebritas TikTok @ravelliobahri - Asmi Nur Aisyah (School of Communication Science and Media Business, 2023)
The presence of TikTok as a social media, as well as a content distribution platform, creates new internet celebrities. Through the work of post-based virality logic, TikTok allows its users to gain popularity through the accumulation of audience interaction (engagement) from each uploaded content. Ravellio Bahri is one of the TikTok celebrities whose popularity has skyrocketed because of his unique profession as a Drag Queen that challenges the dichotomous gender norms. His name even ranks at the top of the search with the keywords 'Indonesian drag queen' on Google. Through qualitative content analysis, this study uses the concept of remediation to explain how a TikTok celebrity Ravellio Bahri remediates gender dichotomy through his profession. By analyzing four selected contents based on the work of post-based virality logic, this study shows that Ravellio remediates gender dichotomy by presenting the entanglement between his profession as a drag queen and his identity as a heterosexual cisgender. This entanglement shows an ambivalence between challenging dichotomous gender norms and establishing gender stereotypes. Keywords: drag queen, TikTok, gender dichotomy, Internet celebrity